BEING SEEN AND LOOKING BACK: MANDATORY ACKNOWLEDGMENT OF SURVEILLANCE FOR LGBTQ+ USERS - Chartrand, Alex (AoIR Selected Papers of Internet Research, 2026)
Digital platforms and social media shape social, economic, and political life, making participation nearly unavoidable (Van Dijck et al., 2018; Steinberg, 2019). This platformization, driven by datafication, records and commodifies user activity for corporate profit (Myers West, 2019). While users perceive their engagement as private, they enact public personas subject to scrutiny, facilitating both commercial and political surveillance (Baym & boyd, 2012; Zuboff, 2015). LGBTQ+ users, in particular, experience a paradox: social media is crucial for identity formation, community-building, and self-expression (Pullen, 2010; Duguay et al., 2023), yet they also face heightened algorithmic surveillance, including shadowbanning, demonetization, and account suspension (Are & Briggs, 2023; Bivens & Haimson, 2016). This study, part of a PhD project, analyzes how LGBTQ+ users in Montréal and Berlin navigate platform regulations and resist algorithmic oppression through qualitative interviews with cultural producers, activists, and performers. Findings highlight two key themes: being seen and looking back. LGBTQ+ users are acutely aware of surveillance, as illustrated by Astra, a Berlin-based activist, whose account was deleted after managing a queer collective’s social media. Faced with inevitable monitoring, users develop strategies—creating backup accounts, using alternative promotional methods, and deliberately defying censorship. Yet, this resistance is exhausting, as Sasha Kills, a Berlin-based drag artist, states: “We don’t have a choice, and it is really unfair.” This research complicates discussions on data justice by illustrating that resistance is not merely emergent but an embedded, mandatory practice for LGBTQ+ users navigating digital spaces.